Wavelet Transform Based Fault Diagnosis of BLDC Motor Drive - Ramesh Balaji S.M.; C. Muniraj; Mekala N (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Due to the development in science and technology tremendous improvement in solid state devices and circuits, so we need to reduce the complexity of control circuits. The Brushless DC Motor (BLDCM) has simple construction, stator consists of winding and rotor consists of permanent magnet. It has higher efficiency and high speed range. In this paper presents the vibration analysis of single phase open circuit fault conditions and the signals are extracted from the Discrete Wavelet Transform (DWT). The Spartan-6 FPGA processor was implemented due to their high performance of the control applications in recent decades. In this process Sinusoidal Pulse Width Modulation (SPWM) techniques were used to control the speed of BLDC Motor. The experimental analysis is carried out in 3phase, BLDCM drive. The vibration signals are measured by using Accelerometer through Lab VIEW software. DOI: http://dx.doi.org/10.11591/telkomnika.v14i3.7967